Relaxor-like and switchable dielectric behavior in a rare noncentrosymmetric 3D iodoargentate hybrid. Issue 89 (12th December 2017) - Yu, Shan-Shan; Liu, Shao-Xian; Zhu, Yi-Xiao; Duan, Hai-Bao; Zhang, H.
Abstract : A rare noncentrosymmetric three-dimensional (3D) iodoargentate hybrid, namely, [Cd(en)3 ]Ag2 I4 (1 ), was prepared using a simple solution process. Abstract : A rare noncentrosymmetric three-dimensional (3D) iodoargentate hybrid, namely, [Cd(en)3 ]Ag2 I4 (1 ), was prepared using a simple solution process. 1 crystallized in the hexagonal space group P 63 22. Its inorganic components formed a novel 3D open-framework structure. 1 is the first 3D iodoargentate hybrid shown to have relaxor-like dielectric behavior and switchable dielectric properties.